Fabrication, Simulation and Characterisation of MEMS Piezoelectric Vibration Energy Harvester for Low Frequency. (2015) - Sharma, A.; Olszewski, O.Z.; Torres, J.; Mathewson, A.; Houlihan, R.
Abstract: A MEMS vibration energy harvester using an Aluminium Nitride (AlN) piezoelectric layer was designed, fabricated and characterized. The harvester was fabricated on an SOI wafer with a 30 μm device silicon layer which serves as the structural beam on which a 0.5 μm AlN layer is sandwiched between the top and bottom electrodes. The handle silicon serves as the proof mass. The harvester has a measured resonant frequency of around 114 Hz and an average output power of 54nW was measured at optimal load and a low level of acceleration (24 mili-g). A 3D finite element model of the harvester was created in COMSOL Multiphysics and the obtained results are in close agreement with the measured data.